Backward classes and the new social order - "Beteille, Andre" (Delhi, 1981)
The Scheduled Castes and Tribes of India form the main component of the 'Backward Classes'-envisaged by the Constitution of India as deserving 'positive discrimination' within an egalitarian society. In this searching and humane inquiry into the merits of differing concepts of equality, the author discusses the extent to which discrimination can benefit a class as a whole, rather than certain individuals.